Channeling the state : community media and popular politics in Venezuela - Schiller, Naomi, 1978- (Radical Américas., 2018)
Venezuela's most prominent community television station, Catia TVe, was launched in 2000 by activists from the barrios of Caracas. Run on the principle that state resources should serve as a weapon of the poor to advance revolutionary social change, the station covered everything from Hugo Chávez's speeches to barrio residents' complaints about bureaucratic mismanagement. This book explores how and why Catia TVe's founders embraced alliances with Venezuelan state officials and institutions. Drawing on long-term ethnographic research among the station's participants, the author shows how community television production created unique openings for Caracas's urban poor to embrace the state as a collective process with transformative potential. Rather than an unchangeable entity built for the exercise of elite power, the state emerges in the author's analysis as an uneven, variable process and a contentious terrain where institutions are continuously made and remade. In Venezuela under Chávez, media activists from poor communities did not assert their autonomy from the state but rather forged ties with the middle class to question whose state they were constructing and who it represented.